340 Assessing the effects of balance training on executive functions and BDNF biomarkers in Alzheimer’s disease patients - Joel Acevedo; Karen Martinez; Claudia Amaya; Liu Kun (Journal of Clinical and Translational Science)
Objectives/Goals: As the aging population increases, maintaining cognitive and physical health becomes crucial. Executive functions (EF), including reaction time, sustained attention, and spatial memory, are essential for daily life and independence in older adults but tend to decline with age, especially in Alzheimer’s disease (AD) patients. Methods/Study Population: Physical balance (PB) impairments further exacerbate this decline, affecting the quality of life and independence. Balance training (BT) emerges as a potential non-pharmacological intervention to enhance EF. This study aims to 1) assess the association between PB impairments and EF deterioration in older adults with AD; 2) evaluate the impact of BT on EF enhancement in this population; and 3) explore changes in brain-derived neurotrophic factor (BDNF) biomarkers before and after physical activity related to BT. This pilot study employs a cross-sectional design with older Hispanic adults (>65 years) in Puerto Rico, comparing a control group without BT intervention to an experimental group with BT intervention. Both groups will be assessed for EF and BDNF biomarkers pre- and post-physical activity. Results/Anticipated Results: Expected outcomes include identifying significant correlations between PB impairment and diminished EF, demonstrating measurable EF improvements following BT, and evidencing sustained BDNF release post-BT despite PB impairments. By understanding the biological mechanisms linking BT and cognitive improvements, particularly the role of BDNF, this research could inform future strategies to mitigate cognitive decline in AD patients through targeted physical interventions. Discussion/Significance of Impact: The findings of this study could provide valuable insights into the development of new preventive interventions, enhancing the quality of life and independence for older adults.